TransferGo : chasing a billion dollar dream - Juknaite, Aiste, (SAGE Knowledge. Cases., 2017)
TransferGo is a company handling online money transfers founded by two Lithuanian young men in the U.K. in September 2012. Within the first two years of its existence, TransferGo made its mark in nearly every European country. In 2014 the founders felt that the time was right to take the leap outside of Europe. They were, however, divided between two fundamentally different approaches towards internationalisation strategy: the incremental revenue-based approach or the radical growth-based approach. Capital from the previous funding round was running low, so a choice had to be made. Should TransferGo take the risk and follow the radical approach, reinforce the team and attract major venture capital in order to grow its business quickly? Or should it follow an incremental revenue-based approach that involves less risk and slower changes? Apart from the discussion around incremental revenue-based internationalisation versus the radical growth-based internationalisation approach, the case also fosters students' understanding of key characteristics and the importance of lean entrepreneurship in the context of an online start-up. Furthermore, it strives to develop both hard and soft skills by letting students create their own business plan and pitch it to the lecturer as well as their peers.